A brutal humanism for the new millennium? The legacy of Neorealism in contemporary cinema of migration. Issue 1 (1st January 2020) - Johnson, Rachel
AbstractThis article proposes that the institutional construction of Italian cinema of migration in the new millennium may be conditioned by an enduring, implicit aspect of Neorealism's legacy: a 'brutal humanism' that posits the witnessing of bodies in crisis as an ethical act. Supplementing Karl Schoonover's theory of brutal humanism with Lacanian gaze theory, I argue that the Berlin International Film Festival's synopsis of a recent cause cæ#169;lèbre of Italian cinema, Fuocoammare (Fire at Sea) (Rosi, 2016), instantiates a 'brutal vision' directed towards the figure of the refugee, while the film text's depiction of the 'objective gaze' of these characters challenges such relations of power and looking. The article underlines the importance of competitive European film festivals and paratexts in the international circulation and ideological construction of Italian cinema, while arguing that the film text itself can offer a site of resistance to the meanings that institutions ascribe to it.